2021
DOI: 10.1371/journal.pone.0257292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seat pan and pelvis angles on the occupant response in a reclined position during a frontal crash

Abstract: Current highly automated vehicle concepts include reclined seat layouts that could allow occupants to relax during the drive. The main objective of this study was to investigate the effects of seat pan and pelvis angles on the kinematics and injury risk of a reclined occupant by numerical simulation of a frontal sled test. The occupant, represented by a detailed 50th percentile male human body model, was positioned on a semi-rigid seat. Three seat pan angles (5, 15, and 25 degrees from the horizontal) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Finite element (FE) human body models (HBMs) are becoming increasingly important numerical tools in vehicle safety for understanding injury mechanisms and developing prevention strategies (Östh et al, 2015;Boyle et al, 2019;Hu et al, 2019;Jakobsson et al, 2019;Pipkorn et al, 2019;Boyle et al, 2020;Hwang et al, 2020;Tang et al, 2020;Grebonval et al, 2021;Leledakis et al, 2021;Larsson et al, 2022;Bohman et al, 2022;Booth et al, 2022;Corrales et al, 2022;Erlinger et al, 2022;Mishra et al, 2022;Piqueras et al, 2022;Putra et al, 2022;Östh et al, 2022). HBMs have advantages over crash test dummies, such as representing varying loading directions, different anthropometries and sex, and muscle tonus (Jakobsson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finite element (FE) human body models (HBMs) are becoming increasingly important numerical tools in vehicle safety for understanding injury mechanisms and developing prevention strategies (Östh et al, 2015;Boyle et al, 2019;Hu et al, 2019;Jakobsson et al, 2019;Pipkorn et al, 2019;Boyle et al, 2020;Hwang et al, 2020;Tang et al, 2020;Grebonval et al, 2021;Leledakis et al, 2021;Larsson et al, 2022;Bohman et al, 2022;Booth et al, 2022;Corrales et al, 2022;Erlinger et al, 2022;Mishra et al, 2022;Piqueras et al, 2022;Putra et al, 2022;Östh et al, 2022). HBMs have advantages over crash test dummies, such as representing varying loading directions, different anthropometries and sex, and muscle tonus (Jakobsson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mendoza-Vazquez et al (2015) also found that injury metrics based on multi-point measurements (DcTHOR and Cmax) were less sensitive to variations in the material properties of the FE-HBM, making these metrics particularly suitable to be used with FE models. Current studies show multiple examples of the application of deformation-based criteria to the prediction of chest injuries using FE-HBM such as Brolin and Wass (2016) , which used DcTHOR and Dmax metrics with the THUMS model for the assessment of the injury protection provided by a safety-vest in equestrian riders, or Grébonval et al (2021) , which used the Cmax and PC Score to compare the thoracic injury risk predicted by the GHBMC HBM and the THOR ATD in frontal impacts in reclined occupant positions.…”
Section: Introductionmentioning
confidence: 99%
“…The most severe and commonly investigated factor occurring in a frontal crash with a reclined seat is submarining-i.e., the occupant's hips sliding under the lap belt, restraining the body at the abdomen [12][13][14]. Submarining causes severe injuries to the lumbar spine and internal organs [15][16][17][18][19]. Accident data analysis shows that the submarining phenomenon is the reason for many fatalities and serious injuries during a frontal impact [20][21][22].…”
Section: Introductionmentioning
confidence: 99%